Analysis The Effect of Regional Expenditure on Economic Growth and Community Welfare in Semarang City 2018-2022 - Pangestu, Dita Idfi; Mutiarin, Dyah; Saputro, Muhammad Noor Cahyadi Eko (Prosiding University Research Colloquium, 2023)
The purpose of this research is to determine the economic growth and welfare of the people of Semarang City from 2018 to 2022 through the coordination of regional spending. A literary study was used in this research, with five main points of discussion: personnel expenditures, capital, goods and services, grants, and social assistance. According to the study’s findings, economic growth is linked to regional spending, with personnel, capital, and social assistance spending all having a positive impact on economic growth. However, several points of regional spending have a less good impact on increasing economic growth in the city of Semarang. Meanwhile, on the public welfare side, regional spending has a positive influence. The influence is obtained on personnel spending, capital, and grants. Each budget has a way to improve welfare such as the construction of a structure that can open job vacancies to impact people’s welfare. With this, the local government must strive to optimize regional spending so that there is significant economic growth and an increase in people’s welfare in the city of Semarang.